Vocal aging: acoustic and articulatory study of speech changes with age - Albuquerque, Luciana Patrícia Martins Nunes Pereira (2022)
Background: Although the aging process causes specific alterations in the speech organs, the knowledge about the age effects in speech production is still disperse and incomplete. Objective: To provide a broader view of the age-related segmental and suprasegmental speech changes in European Portuguese (EP), considering new aspects besides static acoustic features, such as dynamic and articulatory data. Method: Two databases, with speech data of Portuguese adult native speakers obtained through standardized recording and segmentation procedures, were devised: i) an acoustic database containing all EP oral vowels produced in similar context (reading speech), and also a sample of semispontaneous speech (image description) collected from a large sample of adults between the ages 35 and 97; ii) and another with articulatory data (ultrasound (US) tongue images synchronized with speech) for all EP oral vowels produced in similar contexts (pseudowords and isolated) collected from young ([21-35]) and older ([55-73]) adults. Results: Based on the curated databases, various aspects of the aging speech were analyzed. Acoustically, the aging speech is characterized by: 1) longer vowels (in both genders); 2) a tendency for F0 to decrease in women and slightly increase in men; 3) lower vowel formant frequencies in females; 4) a significant reduction of the vowel acoustic space in men; 5) vowels with higher trajectory slope of F1 (in both genders); 6) shorter descriptions with higher pause time for males; 7) faster speech and articulation rate for females; and 8) lower HNR for females in semi-spontaneous speech. In addition, the total speech duration decrease is associated to non-severe depression symptoms and age. Older adults tended to present more depressive symptoms that could impact the amount of speech produced. Concerning the articulatory data, the tongue tends to be higher and more advanced with aging for almost all vowels, meaning that the vowel articulatory space tends to be higher, advanced, and bigger in older females. Conclusion: This study provides new information on aging speech for a language other than English. These results corroborate that speech changes with age and present different patterns between genders, and also suggest that speakers might develop specific articulatory adjustments with aging.